4CPS-261 Analysis of the methodology to communicate potentially inappropriate prescriptions in inpatients to an internal medicine service of a third-level hospital. (March 2019) - Fernandez, M; Carmona, E; Cordero, J; Rendón de Lope, L; Colmenero, MA; Alvarez, L; Calleja, MA
Abstract : Background: For decades, advances in medicine have led to an increase in life expectancy. In Spain, life expectancy is 81 years in men and 85.6 years in woman. This fact has led a high percentage of inpatients over 65 years' old. These patients have often multiple pathologies and the are polymedicated. In these patients it is common to find potentially inappropriate prescriptions (PIP). According to current publications between 25%–30% of patients admitted to the hospital present one or more PIPs. The adequate medication control in these patients makes detection of PIPs crucial in providing adequate healthcare. Purpose: Clinical pharmacists have shown a great capacity in decreasing these PIPs through pharmacist-physician interventions. Our objective is to analyse the possible pharmacist-physician communication channels through which to notify the detected PIPs Material and methods: A 3 month prospective study (February 2018 to April 2018) to analyse the effectiveness of pharmacist-physician communication channels. Effectivity was determined by the% acceptance of the interventions. Channels chosen were: Through direct communication with the physician. Electronic communication using the Farmatools program. Interventions were performed following inadequate prescription, dosage, omissions and duplicates of STOPP/START and Beers criteria. The target population on which the study was conducted were polymedicated patients in an internal medicine service. Results: The medications found in the prescriptions were mainly: nonsteroidal anti-inflammatory drugs (22.1%) antibiotics (22.1%), insulins (19.5%), proton pump inhibitors (10.1%), low-molecular weight heparin (9.4%), digoxin (8.7%) and others (8.1%). Through direct communication with the doctor, the prescriptions of 125 patients over 65 years of age were studied, and pharmacist-physician verbal intervention was performed in 35 of them (28%). 74.3% (n=26) of them were accepted by the physician. Through electronic communication, interventions were performed in 221 patients. Analysing the record of the electronic interventions carried out, only 28.8% (n=62) were accepted. Conclusion: Pharmacist-physician interventions carried out by clinical pharmacists are fundamental for a reduction of PIPs. Direct pharmacist-physician communication provides a greater degree of interventions acceptance rather than electronic intervention. Adding clinical pharmacists to clinical services could help to reduce PIPs. References and/or acknowledgements: No conflict of interest.